Context and culture: Reasons young adults drink and drive in rural America. (December 2018) - Greene, Kaylin M.; Murphy, Samuel T.; Rossheim, Matthew E.
Highlights: Little is known about the reasons rural young people drink and drive. 11 focus groups were conducted with rural young adults ( N = 72) in Montana. An inductive model for drinking and driving was created. Social, cultural, and environmental factors promoted drinking and driving. Unique aspects of the rural context shaped attitudes and beliefs. Abstract: Montana, a large and rural U.S. state, has a motor vehicle fatality rate almost double the national average. For young adults, the alcohol-related motor vehicle fatality rate in the state is almost three times the national average. Yet little research has explored the underlying reasons that young people in rural areas drink and drive. Drawing from the theory of triadic influence (TTI) and a series of qualitative focus group discussions, the current study examined how aspects of the landscape and culture of rural America promote and hinder drinking and driving among young people. In 2015 and 2016, 72 young adults (36 females) aged 18–25 years old (mean age = 20.2) participated in 11 semi-structured focus groups in 8 rural counties in Montana. Discussions were transcribed, and two reviewers independently coded text segments. Themes were identified and an inductive explanatory model was created. The results demonstrated that aspects of the social context (e.g., peer pressure and parental modeling), rural cultural values (e.g., independence, stoicism, and social cohesion), and the legal and physical environment (e.g., minimal police presence, sparse population, and no alternative transportation) promoted drinking and driving. The results also identified salient protective factors in each of these domains. Our findings demonstrate the importance of examining underlying distal determinants of drinking and driving. Furthermore, they suggest that future research and interventions should consider the complex ways in which cultural values and environmental factors intersect to shape the risky health behaviors of rural populations.